1996
DOI: 10.1046/j.1365-3024.1996.d01-10.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a secreted antigen of Onchocerca volvulus with host‐protective potential

Abstract: A cDNA designated MOv2 was isolated from an Onchocerca volvulus library on the basis of its product's recognition by an antiserum raised against the infective stage. Immunogold electron microscopy revealed a high density of antigenic sites associated with the annulae of the L3 cuticle and with the uterine wall of the adult female: a general, low density of labelling occurred in all developmental forms. Western blotting confirmed the presence of the antigen throughout the life cycle and the existence of an immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Immunogold Electron Microscopy with O. volvulus-Adult worms within nodules, developing larvae within blackflies (from day 1 to day 8 post-transmission), and post-infective larvae in culture (described below) were fixed in 2% paraformaldehyde, 0.5% glutaraldehyde in 0.075 M sodium cacodylate buffer and embedded for immunoelectron microscopy, as described (26). Sections (90 nm) mounted on Formvar-coated nickel grids were reacted with rabbit antisera to recombinant Ov-CHI-1 serially diluted from 1:200 to 1:1000 in 1% bovine serum albumin, 0.01% Tween 20 in phosphate-buffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…Immunogold Electron Microscopy with O. volvulus-Adult worms within nodules, developing larvae within blackflies (from day 1 to day 8 post-transmission), and post-infective larvae in culture (described below) were fixed in 2% paraformaldehyde, 0.5% glutaraldehyde in 0.075 M sodium cacodylate buffer and embedded for immunoelectron microscopy, as described (26). Sections (90 nm) mounted on Formvar-coated nickel grids were reacted with rabbit antisera to recombinant Ov-CHI-1 serially diluted from 1:200 to 1:1000 in 1% bovine serum albumin, 0.01% Tween 20 in phosphate-buffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…Several Onchocerca antigens have been evaluated in this model, including two that can be detected in A. viteae ES products (OvB20, and MOv2) and one that is a subunit of O. volvulus tropomyosin (MOv14) (28)(29)(30). All of these antigens induced moderate protection (36 to 60%) against adult worm burdens and exceptional protection against microfilaremia (89 to 97%).…”
Section: Morris Et Almentioning
confidence: 99%
“…Studies with other filarial worms have shown that recombinant antigens can be identified with antibodies from immune serum and that these antigens induced a protective immune response against larval parasites, killing approximately 50% of parasites in the challenge infections (26,35,49). The advantage of using defined recombinant antigens lies in the fact that they can be efficiently and reproducibly generated, whereas irradiated larvae or crude native antigen preparations cannot be practically generated and therefore lack clinical utility.…”
mentioning
confidence: 99%